Agricultural trade between developing countries: patterns and future possibilities - Islam, Nurul (International Food Policy Research Institute, 1992)
Trade between developing countries (intratrade) is often thought to hold considerable potential for future expansion of developing-country exports. However, much of the research in this area has focused on trade in industrial goods; detailed analyses of the past trends and future possibilities for agricultural trade between developing countries has received scant attention.